Directional acuity of whole-body perturbations during standing balance - Puntkattalee, M. Jane; Whitmire, Clarissa J.; Macklin, Alix S.; Stanley, Garrett B.; Ting, Lena H. (Gait & posture, 2016)
•We measured directional acuity of whole-body motion during standing in healthy, young adults.•The directional acuity threshold was about 10° for backward support-surface translations.•An adaptive method requiring fewer trials (∼35 vs. 99) identified similar thresholds.•Computational modeling revealed similar reliability using both techniques. The ability to perceive the direction of whole-body motion during standing may be critical to maintaining balance and preventing a fall. Our first goal was to quantify kinesthetic perception of whole-body motion by estimating directional acuity thresholds of support-surface perturbations during standing. The directional acuity threshold to lateral deviations in backward support-surface motion in healthy, young adults was quantified as 9.5±2.4° using the psychometric method (n=25 subjects). However, inherent limitations in the psychometric method, such as a large number of required trials and the predetermined stimulus set, may preclude wider use of this method in clinical populations. Our second goal was to validate an adaptive algorithm known as parameter estimation by sequential testing (PEST) as an alternative threshold estimation technique to minimize the required trial count without predetermined knowledge of the relevant stimulus space. The directional acuity threshold was estimated at 11.7±3.8° from the PEST method (n=11 of 25 subjects, psychometric threshold=10.1±3.1°) using only one-third the number of trials compared to the psychometric method. Furthermore, PEST estimates of the direction acuity threshold were highly correlated with the psychometric estimates across subjects (r=0.93) suggesting that both methods provide comparable estimates of the perceptual threshold. Computational modeling of both techniques revealed similar variance in the estimated thresholds across simulations of about 1°. Our results suggest that the PEST algorithm can be used to more quickly quantify whole-body directional acuity during standing in individuals with balance impairments.